ANALISIS KESALAHAN SISWA KELAS VII DALAM MENYELESAIKAN SOAL GEOMETRI - Fahrur Rozi Hadiyanto; Hery Susanto; Abd. Qohar (Jurnal Kajian Pembelajaran Matematika, 2019)
Geometry is one of the most important branches of mathematics. At the junior high school level there are several geometry materials taught, including triangles and quadrilaterals. However, in the field, it was found that many students still made mistakes in solving geometry problems. Errors are deviations from the correct solution of a problem, both conceptually and in the procedure for solving it. Errors in solving geometry problems can be used as a reference to find out what difficulties are made by students. One of the efforts in helping students who have difficulty in solving geometry problems is by analyzing the results of students' completion of the problems given. The purpose of this study was to determine the types and causes of student errors in solving geometry problems. This study used a qualitative approach by using a test question instrument. The subjects of this study were 3 of 33 students of class VII A MTs Surya Buana Malang. From the results of the analysis of student answers and interviews conducted, it was obtained data that the types of errors made by students included: conceptual errors, procedural errors and errors in understanding the questions. Conceptual errors made by students include: error types of triangles, properties of quadrilaterals, definitions of quadrilaterals, concepts of operations on numbers, and concepts of perimeter and area of triangles and quadrilaterals. Procedural errors made by students are errors in giving units of circumference or area and calculation errors. And errors in understanding the problem. While the causes of these errors include students who are less able to distinguish between angles and line segments, are less able to distinguish types of triangles based on angles and based on sides, do not understand the concept of operations on numbers, are less precise, do not understand the difference in area and the number of angles in triangles, lack of variety of questions. given by the teacher and do not understand the perimeter and area of a quadrilateral.